The Way of Measuring Transmission Efficiency of Gearing on a Gear Tester with Mechanical closed Power - 孟玲茹; 张磊 (Jixie chuandong)
A way of measuring transmission efficiency of gearing on a gear tester with mechanical closed power is given,and the formulas of calculating thetransmission efficiency of gear reducer from the testing results are developed.